2019
DOI: 10.1371/journal.pone.0221800
|View full text |Cite|
|
Sign up to set email alerts
|

Flowers as viral hot spots: Honey bees (Apis mellifera) unevenly deposit viruses across plant species

Abstract: RNA viruses, once considered specific to honey bees, are suspected of spilling over from managed bees into wild pollinators; however, transmission routes are largely unknown. A widely accepted yet untested hypothesis states that flowers serve as bridges in the transmission of viruses between bees. Here, using a series of controlled experiments with captive bee colonies, we examined the role of flowers in bee virus transmission. We first examined if honey bees deposit viruses on flowers and whether bumble bees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 48 publications
(57 reference statements)
5
58
0
Order By: Relevance
“…BQCV, DWV-A and DWV-B have been frequently detected in bumblebees (Bombus spp. ; [19,24,26,27,29,39,40] and other wild bee species collected from the field (reviewed in [25]), as well as in other insect species associated with honeybees or the flowers they visit (e.g. [54][55][56][57][58]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BQCV, DWV-A and DWV-B have been frequently detected in bumblebees (Bombus spp. ; [19,24,26,27,29,39,40] and other wild bee species collected from the field (reviewed in [25]), as well as in other insect species associated with honeybees or the flowers they visit (e.g. [54][55][56][57][58]).…”
Section: Discussionmentioning
confidence: 99%
“…are widespread wild bee species in northern temperate regions [36], yet many are decreasing in abundance or distribution, with parasites being a potential cause of their decline [37,38]. BQCV is the most prevalent virus in bumblebees [24,26,29,30], it exhibits broad tissue tropism in the American Bombus huntii [39,40], and its prevalence in Bombus spp. covaries with that in Apis.…”
Section: Introductionmentioning
confidence: 99%
“…Although no study to date has reported the presence of viruses in the feces of non-Apis species, one could expect that virus particles are shed via the feces, similar to how this happens in honey bees. Several studies have directly identified the role of shared flowers in the transmission of a number of bee pathogens, including viruses (Singh et al, 2010;Graystock et al, 2015;Adler et al, 2018;Alger et al, 2019). Therefore, infected bees visiting flowers can contaminate the flower surface, nectar and pollen with virus particles they shed via their feces.…”
Section: Inter-species Virus Transmissionmentioning
confidence: 99%
“…Eusocial non-Apis species belong to the tribes Meliponini (stingless bees) and Bombini (bumble bees). Both tribes have a social structure similar to honey bees, with a single reproductive (Singh et al, 2010;Alger et al, 2019), depicted in the middle surrounded by a red dotted line. Inter-and intra-species transmission in non-social bees, depicted on the left side can occur through contact at nest aggregations or the reuse of virus-contaminated old nest cavities (Krunicì and Stanisavljevicì, 2006).…”
Section: Intra-species Transmissionmentioning
confidence: 99%
“…One of the most prevalent honey bee viruses is Black queen cell virus (BQCV) [32][33][34], so-called because it kills developing queen honey bee larvae, whose necrotic remains blacken their pupal cells [35][36][37]. Nurse honey bees horizontally transfer BQCV from infected cells to healthy larvae in brood food [38], and queens may also vertically transmit it to eggs [9].…”
Section: Introductionmentioning
confidence: 99%